Foreign Constitutional Guarantee of Voting Right - Troyan, Vladimir A.; Kuznetsov, Alexander A.; Novikova, Alevtina E.; Tkhabisimova, Lyudmila A.; Zemlyanoy, Alexey V. (International Journal of Criminology and Sociology, 2022)
The paper presents the results of a comparative legal study of the texts from the constitutions belonging to the member countries of the Commonwealth of Independent States to identify guarantees of legal voting right in them. The study was built based on a dialectical approach to disclosing legal phenomena and processes using general scientific (systemic, logical, analysis, and synthesis) and particular scientific methods. Based on the classification method, the sought guarantees were identified, named, and characterized in the following varieties: constitutional sovereign, electoral constitutional with a subdivision into the material (general and particular) and procedural (restrictive and technical) types, and institutional guarantees implemented by special and constitutional control entities as well as standardizing constitutional types. Within this working framework, the authors present the results of the comparative study devoted to the constitutions of the CIS member states in connection with the identification of guarantees of legal voting right in them. So far, no such comparative study has been conducted to identify the securities of the right to vote in the member states of the Commonwealth of Independent States.